The American spirit [large type] : who we are and what we stand for - McCullough, David G. (Thorndike Press, a part of Gale, a Cengage Company, 2017)
This collection of speeches by historian David McCullough reminds us of fundamental American principles. Over the course of his distinguished career, David McCullough has spoken before Congress, the White House, colleges and universities, historical societies, and other esteemed institutions. Now, as many Americans engage in self-reflection following a bitter election campaign that has left the country divided, McCullough has collected some of his most important speeches in a brief volume that articulates important principles and characteristics that are particularly American.